Analysis of RGS2 expression and prognostic significance in stage II and III colorectal cancer. Issue 6 (24th September 2010) - Jiang, Zheng; Wang, Zhimin; Xu, Ye; Wang, Beilan; Huang, Wei; Cai, Sanjun
Abstract : The role of RGS2 (regulator of G-protein signalling 2) has been studied in several tumours. The purpose of the present study is to investigate the correlations between clinicopathological factors and patients' survival time and RGS2 expression in stage II and III CRC (colorectal cancer) patients. Real-time quantitative PCR was performed in 36 CRC tissues with recurrence and 28 without recurrence, and in three CRC-metastasis-derived cell lines (SW620, LoVo and Colo205) and 3 primary-CRC-derived ones (SW480, Caco-2 and HCT116) to examine RGS2 mRNA expression. In addition, to provide visualized evidence for RGS2 mRNA expression, random CRC samples were also performed with RT–PCR (reverse transcription–PCR). RGS2 protein was detected by immunostaining in 118 paraffin-embedded specimens, and the correlations between clinicopathological factors and survival time and RGS2 expression were analysed. We found that RGS2 mRNA was down-regulated both in CRC tissues with recurrence and metastasis-derived cell lines, and the expression level of RGS2 was unrelated to gender, age, tumour grade, or lymphovascular or perineural invasion. However, it was positively related to disease-free survival time ( P <0.05). Furthermore, low RGS2 expression indicated a poorer survival rate ( P <0.05, log-rank test). Multivariate analysis also showed that weak RGS2 protein expression was an independent adverse prognosticator in CRC ( P <0.05). Taken together, we suggested that down-regulation of RGS2 might play an important role in CRC metastasis and predict poor prognosis in stage II and III CRC patients.